2018
DOI: 10.3389/fmicb.2018.02202
|View full text |Cite
|
Sign up to set email alerts
|

Chinese Black Truffle (Tuber indicum) Alters the Ectomycorrhizosphere and Endoectomycosphere Microbiome and Metabolic Profiles of the Host Tree Quercus aliena

Abstract: Truffles are one group of the most famous ectomycorrhizal fungi in the world. There is little information on the ecological mechanisms of truffle ectomycorrhizal synthesis in vitro. In this study, we investigated the ecological effects of Tuber indicum – Quercus aliena ectomycorrhizal synthesis on microbial communities in the host plant roots and the surrounding soil using high-throughput sequencing and on the metabolic profiles of host plant roots using metabolomics approaches. We observed an increase in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 92 publications
(115 reference statements)
4
44
0
Order By: Relevance
“…The most abundant genera of AOB were Nitrosospira and Nitrosomonas. Li et al (2018a) and Li et al (2018b) reported that the Nitrosospira and Nitrosomonas were the most abundant AOB in ectomycorrhizosphere soil of Pinus massoniana Lamb colonized by Pisolithus tinctorius under field condition, which is basically the same with the findings of our study. In addition, the relative abundance of Nitrosococcus and an unclassified AOB genus of Betaproteobacteria in ectomycorrhizosphere soils was significantly greater than that in rhizosphere soils while another unclassified genus was significantly lower than that in rhizosphere soils (P < 0.05).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The most abundant genera of AOB were Nitrosospira and Nitrosomonas. Li et al (2018a) and Li et al (2018b) reported that the Nitrosospira and Nitrosomonas were the most abundant AOB in ectomycorrhizosphere soil of Pinus massoniana Lamb colonized by Pisolithus tinctorius under field condition, which is basically the same with the findings of our study. In addition, the relative abundance of Nitrosococcus and an unclassified AOB genus of Betaproteobacteria in ectomycorrhizosphere soils was significantly greater than that in rhizosphere soils while another unclassified genus was significantly lower than that in rhizosphere soils (P < 0.05).…”
Section: Discussionsupporting
confidence: 90%
“…Soil microorganisms and physicochemical properties in the rhizosphere of host plant can vary with the growth of truffles, from the occurrence of ectomycorrhizae to the formation of their mature fruiting bodies (Ponce et al, 2014;Barbieri et al, 2007;Garcia-Barreda et al, 2017). The microbial communities of ectomycorrhizosphere soils are verified to be different from that of rhizosphere soils in both artificial conditions and the wild Li et al, 2018a;Li et al, 2018b). There were numerous classified and unclassified microorganisms detected in the ectomycorrhizosphere soils of Tuber (Garcia-Barreda & Reyna, 2012), which made it difficult to analyze the taxonomy and function of all the bacteria simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…T. melanosporum grounds also have shown a reduced fungal biodiversity, a reduced presence of both ECM Basidiomycota (57). Truffle-colonization reduced the abundance of some fungal genera surrounding the host tree, such as Acremonium (55). Russula fruiting body decreased the Chao richness bacterial index and Shannon diversity of bacterial index in rhizosphere soil.…”
Section: Discussionmentioning
confidence: 99%
“…The microorganisms associated with mycorrhizal fungi may either have positive or negative impacts on fungal spore germination, growth, nutrient acquisition and plant colonization (43, 54). Tuber indicum altered the ectomycorrhizosphere and endoectomycosphere microbiome and metabolic profiles of the host tree Quercus aliena (55). Tuber borchii shapes the ectomycorrhizosphere microbial communities of Corylus avellana (56).…”
Section: Importancementioning
confidence: 99%
“…Previous researches have explored the microbiome composition of some tru es and the physiology of associated trees by studying a single host species. For example, Tuber indicum can shape microbiome in ectomycorhizophere soil in a Pinus armandii forest while in uence the host physiology in a Quercus acutissima stand [2] and metabolic pro les in a Q. aliena stand [3]. Microbiome`s long-term stability is vital due to the fact that the uninterrupted presence of bene cial microbes and their associated functions guarantee host health and tness.…”
Section: Introductionmentioning
confidence: 99%